The Enjoyability of Physical Exercise: Exergames and Virtual Reality as New Ways to Boost Psychological and Psychosocial Health in Astronauts. A Prospective and Perspective View - Gianmarco Ciocca; Harald Tschan (IEEE Open Journal of Engineering in Medicine and Biology)
On Earth, physical activity plays a tremendous role to preserve and improve the physical, psychological, and social well-being of people. The enjoyability, the appreciation, and the variability of the exercises are fundamental factors for the production of lifestyle benefits. Currently, exercise countermeasures for astronauts during long-duration missions focus more on the physiological side, frequently overlooking the relevant psychosocial one. Exergames are a form of physical activity that have taken hold in the last decades on Earth and has been widely accepted as a more enjoyable and engaging rehabilitation, reconditioning, and training tool compared to the previous conventional ones. After a review of the current needs of astronauts and of the positive effects of exergames on people on Earth, we suggest that exergaming should be implemented in space missions to improve physical, psychological, and social well-being of astronauts. We also propose practical methods on how exergames can be effectively implemented.